The Relationship Of Mother's Knowledge of Nutritional Information and Attitude Through Social Media with Family Food Patterns at Posyandu Mawar - Novianty (IKesT Muhammadiyah Palembang, 2023)
Introduction: Knowledge is the result of knowing which is a concept in a person's mind as a result of someone sensing a certain object. Nutritional knowledge is the main problem that occurs in society regarding various nutritional problems that occur in Indonesia. Indirectly, the mother's knowledge will influence the nutritional status of her family. Knowledge influences the mother in providing food for her family, the better the mother's knowledge, the better the family's diet, because the mother is the originator of the family food, from the one who prepares it, chooses the menu for the family. Research Objective: The aim of this research is to determine the relationship between knowledge of nutritional information and maternal attitudes via social media towards family food patterns at Diposyandu Mawar. Method: used in this research is analytical descriptive with a cross sectional approach using interview and questionnaire methods. Conclusion: The conclusion of this research is that there is a relationship between knowledge and attitudes towards family eating patterns. because the mother determines the food supply in the family which can determine the nutritional status of the family.